2020
DOI: 10.22363/2313-0660-2020-20-4-698-706
|View full text |Cite
|
Sign up to set email alerts
|

Farmers-Herdsmen Conflict in Africa: The Case of Nigeria

Abstract: General population growth and an increase in the number of farmers, environmental degradation, disruption of conditions for resolving land and water disputes, and the proliferation of Small Arms and Light Weapons (SALW) in the Sahel and West Africa have exacerbated the struggle for the survival and security of economic livelihoods, and in particular negatively affected relationships between shepherds and farmers in several communities in Africa. This kind of conflict between farmers and herdsmen mainly applies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…In this case,the farm size with coefficient (β1 =3.805) implies that a reduction in the size of the farm by one hectare would cause a decrease in the output level by 3.805. The struggle between the farmers and herders on the limited available farmlands has been observed also by various researchers as a major factor responsible for the incessant farmers-herders conflicts (Oghuvbu & Oghuvbu, 2020;Hyginus, 2022 andAjibo et al, 2018). Furthermore, the analysis identified other factors that affect the output of rice in the area, including the the amount of seeds used (β2 =0.164) and pesticides (β6 =1.387).…”
Section: Factors Influencing the Production Of Rice In The Area As A ...mentioning
confidence: 88%
See 1 more Smart Citation
“…In this case,the farm size with coefficient (β1 =3.805) implies that a reduction in the size of the farm by one hectare would cause a decrease in the output level by 3.805. The struggle between the farmers and herders on the limited available farmlands has been observed also by various researchers as a major factor responsible for the incessant farmers-herders conflicts (Oghuvbu & Oghuvbu, 2020;Hyginus, 2022 andAjibo et al, 2018). Furthermore, the analysis identified other factors that affect the output of rice in the area, including the the amount of seeds used (β2 =0.164) and pesticides (β6 =1.387).…”
Section: Factors Influencing the Production Of Rice In The Area As A ...mentioning
confidence: 88%
“…Ajibo et al (2018) also reported that the porous nature of Nigerian borders, over-concentration of infrastructure in urban centers, ineffective security response, and lack of political will to address the issue are the factors that aid herders-farmers conflicts in Nigeria. Moreover, Oghuvbu and Oghuvbu (2020) noted that conflicts between farmers and herders in most African countries have been worsened by factors such as rapid population growth, an increase in people engaging in farming as a means of livelihood, environmental degradation, indiscriminate grazing by herders, and the proliferation of Small Arms and Light Weapons. Beetseh (2018) reported that deforestation and uncontrolled pastoralism contribute to the ongoing conflict between farmers and herders.…”
Section: Introductionmentioning
confidence: 99%
“…Herders move from the northern part southward to the middle belt and coastal zones in Nigeria, in search of greener pasture and fresh water for their cattle. This is due to longer rainy season and ability of the soil to retain moisture for long in the middle belt and southern parts of Nigeria (Ofuoku and Isife 2010;Oli, Ibekwe and Nwankwo, 2018;Oghuvbu and Oghuvbu, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several cases of killing, maiming, animal rustling, crop farm destruction by herders' animals among other have been reported as a result of such clashes. Though, climate change scenario has its own stake in the causes of inadequate fodder for animals, the technological development and medical research which brought about the various e development of veterinary drugs and vaccines to cure sleeping sickness in cattle contributes to the continuous depletion of forest resources in feeding animals (Zoomers and Noorloos, 2013;Oghuvbu and Oghuvbu, 2020;Lezuya, 2021). This development has enhanced the sustaining domestication of the cattle in the southern parts of Nigeria which was formerly unconducive for the animals due to the presence of tsetse flies that inflict sleeping sickness on the cattle.…”
Section: Loss Of Biodiversitymentioning
confidence: 99%